Validação da espécie Colossoma macropomum (Cuvier, 1818) como organismoteste para o uso em ensaios ecotoxicológicos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
In recent decades, population growth and various human activities have gradually contributed to the degradation of terrestrial and aquatic ecosystems, and the excessive use of pesticides/agricultural pesticides stands out in this process. Pesticides have a high potential to be transported in different environmental matrices. To assist in environmental quality studies, ecotoxicology has developed several test methods using test organisms sensitive to contaminants. The present study aimed to evaluate the viability of the species Colossoma macropomum as a test organism for use in ecotoxicological assays with emphasis on acceptability criteria, under the scope of NBR 15088: ABNT, 2016. Sensitivity assays were carried out (in total 10 repetitions) with the reference substance, potassium dichromate (Kr2Cr2O7) and the averages of the LC50-96H of each assay were used for the elaboration of the control chart, a graph that includes a central line, an upper control limit and a bottom control. Using the same batches of test organisms, acute toxicity tests were performed in parallel and the mean lethal concentrations (LC50-96H) were determined for three individual chemicals: chlorpyrifos, imidacloprid and glyphosate. It is noteworthy that initially preliminary tests were carried out to determine the definitive concentrations of potassium dichromate, as well as other toxic substances. Physical-chemical analysis of the water was also performed: pH, dissolved oxygen, temperature, ammonia and total alkalinity. The general mean LC50-96H determined from the sensitivity tests with potassium dichromate was equal to 38.1 mg/L, and the acute toxicity tests with the pesticides: chlorpyrifos, imidacloprid and glyphosate, had LC50-96H values equal to 50.1 µg/L, 37.29 mg/L and 8.25 mg/L, respectively. The results showed that C. macropomum juveniles are sensitive to the chemical substances to which they were exposed in this study, and are a promising animal model to be used in acute toxicity tests.
Keywords: Carta de sensibilidade; Substâncias químicas; Toxicidade aguda; Tambaqui; CNPQ::CIÊNCIAS DA SAÚDE::FARMÁCIA::TECNOLOGIA FARMACÊUTICA; Fisiologia ambiental